Testing speaking - Zieglerová, Kateřina (Univerzita Pardubice, 2011)
In my thesis I deal with the problem of testing speaking. Mainly, I focus on particular techniques that elicit speaking to make the testing process effective. The practical part depicts the realization of testing speaking process in the primary school environment. The central focus is directed at the used elicitation techniques.
Ověřování dovednosti mluvení
Keywords: hodnocení; žáci; komunikativní kompetence; řečové dovednosti; assessment; candidate; communicative competence; interview; oral presentation; language skills; simulations; tests; rozhovory; mluvená prezentace; simulace; testy